Effect of ultrasonic peening on mechanical properties of low carbon steel AISI 1020 TIG welding joints process - Mohammed Ali, Ghusoon Ridha; Ridha, Ali Zuhair; Sadeq, Dina Abbas; Ebraheem, Ahmed Abdullah; Atta, Amal Sadeq (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the effect of ultrasonic peening surface treatment on the mechanical properties of TIG butt weld joints of low-carbon steel (AISI 1020) was studied. A single V-angle was made on sheets of metal used then welded at constant parameters, namely: current, voltage.
Keywords: low carbon steel; gas tungsten arc; ultrasonic peening; mechanical properties